Civic Engagement in the Wake of Katrina - Koritz, Amy (The New Public Scholarship, 2009)
"Civic engagement has been underrated and overlooked. Koritz and Sanchez illuminate the power of what community engagement through art and culture revitalization can do to give voice to the voiceless and a sense of being to those displaced." ---Sonia BasSheva Mañjon, Wesleyan University "This profound and eloquent collection describes and assesses the new coalitions bringing a city back to life. It's a powerful call to expand our notions of culture, social justice, and engaged scholarship. I'd put this on my 'must read' list." ---Nancy Cantor, Syracuse University "Civic Engagement in the Wake of Katrina is a rich and compelling text for thinking about universities and the arts amid social crisis. Americans need to hear the voices of colleagues who were caught in Katrina's wake and who responded with commitment, creativity, and skill." ---Peter Levine, CIRCLE (The Center for Information & Research on Civic Learning & Engagement) This collection of essays documents the ways in which educational institutions and the arts community responded to the devastation wrought by Hurricane Katrina. While firmly rooted in concrete projects, Civic Engagement in the Wake of Katrina also addresses the larger issues raised by committed public scholarship. How can higher education institutions engage with their surrounding communities? What are the pros and cons of "asset-based" and "outreach" models of civic engagement? Is it appropriate for the private sector to play a direct role in promoting civic engagement? How does public scholarship impact traditional standards of academic evaluation? Throughout the volume, this diverse collection of essays paints a remarkably consistent and persuasive account of arts-based initiatives' ability to foster social and civic renewal. Amy Koritz is Director of the Center for Civic Engagement and Professor of English at Drew University. George J. Sanchez is Professor of American Studies and Ethnicity and History at the University of Southern California. Front and rear cover designs, photographs, and satellite imagery processing by Richard Campanella. digitalculturebooks is an imprint of the University of Michigan Press and the Scholarly Publishing Office of the University of Michigan Library dedicated to publishing innovative and accessible work exploring new media and their impact on society, culture, and scholarly communication. Visit the website at www.digitalculture.org.